Elastic hydrogel as a sensor for detection of mechanical stress generated by single cells grown in three-dimensional environment. (August 2016) - Huang, Jianyong; Wang, Liangli; Xiong, Chunyang; Yuan, Fan
Abstract: Cell volume growth occurs in all living tissues. The growth exerts mechanical stresses on surrounding tissues that may alter tissue microenvironment, and have significant implications in health and diseases. However, the level of growth stress generated by single cells in three-dimensional (3D) environment remains to be determined. To this end, we developed a growth force microscopy technique to determine 3D distribution of the stress. The technique was based on encapsulation of cells in elastic hydrogels, and involved 3D particle tracking and mechanical analysis of gel deformation. Data from the study demonstrated that the growth stress was dynamic, and the stress distribution at the gel-cell interface was correlated inversely to the mean surface curvature or the distance to the geometric center of the cell. The stress averaged over the cell surface increased with increasing gel stiffness, suggesting that cells could alter growth stress in response to stiffness change in microenvironment. These findings suggested that the elastic hydrogel-based microscopy technique had a potential to provide new insights into mechanisms of mechanical interactions between cell and its microenvironment.